Insertion Loss Estimation of EMI Filters in Unmatched Input/Output Impedance System - Drinovsky, Jiri; Kejik, Zdenek; Ruzek, Vaclav; Zachar, Jiri; Svacina, Jiri (Společnost pro radioelektronické inženýrství, 2011)
One of the problems in the design of powerline EMI filters is the uncertainty and ambiguity of their source/load impedances which results in breach of expected filter parameters in a real installation. The paper presents a simple technique for prediction of insertion loss limit values of EMI filters working in arbitrary unmatched mains line impedance systems.
Keywords: EMI mains filter; insertion loss; estimation; impedance termination; unmatched impedance system